Analysis of The Effect of Artificial Intelligence (AI) And Hedonism Lifestyle On Loan Decisions Using Spaylater With Self-Control As An Intervening Variable - Findia Idamazari; Sri Hermuningsih; Risal Rinofah (Journal of Economy, Accounting and Management Science (JEAMS), 2026)
This study aims to test and analyze (1) the influence of AI (Artificial Intelligence) on loan decisions using Shopee PayLater, (2) the influence of Hedonism Lifestyle on loan decisions using Shopee PayLater, (3) the influence of AI (Artificial Intelligence) on loan decisions using Shopee PayLater through self-control, (4) the influence of Hedonism Lifestyle on loan decisions using Shopee PayLater through self-control, and (5) the influence of Self-Control on loan decisions using Shopee PayLater. The sample in this study was 130 respondents from Generation Z in Yogyakarta who were active Shopee users and had made transactions using SPayLater at least once in the past month. The data collection method employed a distributed questionnaire, and the sampling technique used was purposive sampling. This study used Outer Model analysis techniques, Model Fit Test, and Inner Model Analysis. The analysis tool used SmartPLS 4.1.0.9. The results of the study show (1) there is no positive and significant influence of the Artificial Intelligence variable on the loan decision using Shopee PayLater (2) there is a positive and significant influence of the Hedonism Lifestyle Variable on the loan decision using Shopee PayLater (3) there is a positive and significant influence of Artificial Intelligence on the loan decision using Shopee PayLater through self-control (4) there is a positive and significant influence of the Hedonism Lifestyle on the loan decision using Shopee PayLater through Self-control (5) there is a positive and significant influence of the Self-Control variable on the loan decision using Shopee PayLater.